Shahifah Madinah: Sistem Bernegara Menurut Rasulullah SAW. - Hemawati Hemawati; Katimin Katimin; Ardiansyah Ardiansyah; T. Wildan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Shahifah Madinah: A State System According to the Prophet Muhammad SAWShahifat al-Madinah as a reference for the model of state life at the time of the Prophet Muhammad can be found in two books, namely: the book of Al-Amwal and in the book of sirah nabawiyah ibn Hisham. In previous research, it is stated that in the book of Al-Amwal, although the hadith has a sanad, there are two narrators who are considered weak (mursal), while in the book of Ibn Hisham, there is no sanad. To find out the existence of the contents of the shahifah in the hadith so that it can be used as a guide, it is necessary to study it from the perspective of the hadith. The purpose of this study is to find out the state system in Shahifat al-Madinah and to find out the hadiths containing the texts/manuscripts of Shahifat al-Madinah. This research used a library approach with the method of content analysis (content analysis) on the Shahifat al-Madinah. The results show that the main book 9 encyclopedia can be found in the book Sahih al-Bukhari no. 6756, Sunan Abu Daud no. 2606, Musnad Ahmad Ibn Hambal No. 913, 1231 and 1330, 8808, 9432. However, there are related hadiths in it as follows: Sahih al-Bukhari no. 1737, 1740, 2936, 2943,6258, Sahih Muslim no. 2429, 2433, 2434,2435, 2774, Sunan Tirmidzi no. 2053, Sunan Abu Daud no. 1739, Musnad Imam Ahmad Bin Hanbal no. 581, 986, 6920, 8808, 10384, 13012, 16112